Rancang Bangun Sistem Konversi Energi Panas Bumi Berbasis Heat Exchanger untuk Aplikasi Rumah Tangga - Arif Febriansyah Pasaribu; Aldi Vebrianto Situmorang; Suhada Juliansyah Nasti; Oktavianus Pratama Situmorang (Pusat riset dan Inovasi Nasional, 2025)
Indonesia has great potential in the use of geothermal energy as a source of renewable energy. However, its application at the household scale is still very limited. This study designed a geothermal energy conversion system using a shell and tube type heat exchanger that is optimized for domestic needs. This system uses an isopentane working fluid that has a low boiling point, thus allowing the efficient use of low-thermal heat for water and room heating. The simulation results show that this system has a high heat transfer efficiency, with an output temperature of up to 84°C. Thus, this system has the potential to become an economical and environmentally friendly renewable energy solution for households.